(untitled) - Nguyễn, Văn Hiếu (Hà Noi, 1999)
Contents: Non-relativistic fermions; superconducting pairing of fermions on soilds; system of strongly correlated electrons in the lattice.
Keywords: Calculus,integral,Phương trình vi phân; Problems, exercises, etc.,Câu hỏi và bài tập